2021
DOI: 10.7150/jca.51851
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of lncRNA‑associated ceRNA network in melanoma

Abstract: Melanoma is an extremely malignant tumor with early metastasis and high mortality. Little is known about the process of by which melanoma occurs, as its mechanism is very complex and only limited data are available on its long non-coding RNA (lncRNA)-associated competing endogenous RNAs (ceRNAs). The purpose of this study was to screen out potential prognostic molecules and identify a ceRNA network related to the occurrence of melanoma. We screened 169 differentially expressed mRNAs (DEmRNAs) from E-MTAB-1862 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…let-7b was significantly decreased in melanoma compared to benign melanocytic lesions and also presented a significant association with key clinicopathological factors, such as Breslow index, ulceration, and AJCC pT staging [ 60 ]. let-7a-5p expression was previously reported to be directly correlated with OS standing as an independent prognostic factor in melanoma [ 61 ] but was inversely correlated with OS in lung malignant tumors [ 62 ]. High expression was also found to prevent lung adenocarcinoma by inhibiting keratin 5 (KRT5) expression [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…let-7b was significantly decreased in melanoma compared to benign melanocytic lesions and also presented a significant association with key clinicopathological factors, such as Breslow index, ulceration, and AJCC pT staging [ 60 ]. let-7a-5p expression was previously reported to be directly correlated with OS standing as an independent prognostic factor in melanoma [ 61 ] but was inversely correlated with OS in lung malignant tumors [ 62 ]. High expression was also found to prevent lung adenocarcinoma by inhibiting keratin 5 (KRT5) expression [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of let-7a-5p is known to influence cancer aggressiveness. In colorectal cancer, let-7a-5p downregulation can be predictive of a worse outcome [ 61 ] by enhancing proliferation and vascular invasion [ 64 , 65 ]. NEAT1 ( Nuclear paraspeckle assembly transcript 1 ), a long noncoding RNA, was reported to interact with let-7a-5p, with both being inversely correlated [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In MM, most of the differentially expressed genes were associated with EMT. LINC00520 can promote EMT by regulating the LINC00520/let-7a-5p/DTL axis ( 17 ).…”
Section: The Cerna Network Of Linc00520 In Cancermentioning
confidence: 99%
“…LINC00520 is abnormally upregulated in 11 cancers, including lung cancer (11), non-small cell lung cancer (NSCLC) (10), lung adenocarcinoma (LUAD) (12,13), breast cancer (BC) (4,8), papillary thyroid carcinoma (PTC) (14), colorectal cancer (CRC) (15), melanoma (MM) (16)(17)(18), head and neck squamous cell carcinoma (HNSCC) (19), laryngeal squamous cell carcinoma (LSCC) (20), glioma (9), nasopharyngeal carcinoma (NPC) (21), etc. Further in vitro experiments have shown that LINC00520 significantly promotes tumor progression by controlling the proliferation and other biological functions of cancer cells (14,21) (Table 1).…”
Section: The Aberrant Expression Of Linc00520 In Cancermentioning
confidence: 99%
“…Skin Cutaneous Melanoma (SKCM) is a primary malignant tumor that originates from benign moles ( Cramer, 1991 ). It is derived from neural crest stem cells, which can produce melanin in the skin ( Ding et al, 2021 ). Nevis will not develop into melanoma in most cases ( Damsky and Bosenberg, 2017 ).…”
Section: Introductionmentioning
confidence: 99%